2021
DOI: 10.1101/2021.04.04.21254889
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of repeated injection of 1% lidocaine vs. radial extra-corporeal shock wave therapy for treating myofascial trigger points: a randomized controlled trial

Abstract: Purpose: To compare the efficacy of radial extracorporeal shockwave therapy (rESWT) versus injection of 1% lidocaine for active myofascial trigger points (MTPs) at upper trapezius muscle (UTM) objectively with elastic index analysis. Patients and methods: A prospective, randomised, single-blinded clinical trial was done. 60 patients with active MTPs of UTM were randomised to receive either rESWT (n = 30); three rESWT sessions; one session per week; 2000 rESWT impulses per session; positive energy flux density … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
(165 reference statements)
0
2
0
Order By: Relevance
“…The second take-home message of this study is that different tissues respond to the same mechanical stimulus in different ways. Based on many years of clinical experience and numerous clinical studies, various pathologies of the musculoskeletal system are nowadays known that can be successfully treatet with ESWT [8][9][10][11]200,227,229]. These indications include mainly degenerations and injuries of muscle, bone and cartilage tissue.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The second take-home message of this study is that different tissues respond to the same mechanical stimulus in different ways. Based on many years of clinical experience and numerous clinical studies, various pathologies of the musculoskeletal system are nowadays known that can be successfully treatet with ESWT [8][9][10][11]200,227,229]. These indications include mainly degenerations and injuries of muscle, bone and cartilage tissue.…”
mentioning
confidence: 99%
“…Furthermore, it cannot be excluded that ESWT is influencing the conduction ability of sensitive nerves through activation of gate control mechanisms in the spinal cord [228]. Compared to neural therapy, a recent study demonstrated that in patients with myofascial trigger points in the upper trapezius, both repeated injection of 1% lidocaine and rESWT resulted in reduced pain alongside improved muscle elasticity, pressure pain threshold and neck disability index [229].…”
mentioning
confidence: 99%